Strategies for preventing the decline of peripheral areas - Martin Boesch; Erich Renner; Dominik Siegrist (Revue de Géographie Alpine)
The gap between urban centres and peripheral areas is widening and the depopulation of remote regions is increasing. In the less appealing areas, infrastructures and production plants are being wound up or, at east, not developed at the same rhythm as in urban agglomerations. Switzerland’s New Regional Policy (NRP) focuses more intensely on the economy than the previous policies did. It no longer targets regional balance, or maintenance of regional occupation in decentralized areas thus preventing depopulation of mountain regions, but is focusing on promoting economic centres. Although a sustainable regional policy must be implemented, it is also fundamental to define clear objectives and a range of conclusive measures for the peripheral areas. At the same time, the obstacles of the sectoral policy still in effect today, must be overcome. It remains to be seen what is likely to happen in regions that have been substantially and structurally weakened by decades of depopulation; regions where investors prefer not to venture to develop resources that are still available. Regional policy must discuss this issue openly, and also determine how a desired and structured decline may be implemented in certain regional areas. It would be considered highly ineffective to avoid such a subject, as this decline has been progressing for a long time, silently, quite invisibly, and in a totally disorganized manner until now.